A self-assembly solvothermal synthesis of SiMoVn@[Cu6O(TZI)3(H2O)6]4·nH2O for the efficient selective oxidation of various alkylbenzenes. (27th April 2022) - Liu, Jiabin; Xin, Yuxiang; Bai, Yiyang; She, Wei; Wang, Jing; Li, Gaungming
Abstract : A series of SiMoV n @ rht -MOF-1 were isolated via a one-pot self-assembly solvothermal synthesis, exhibiting effective catalytic activity and excellent recyclability. Abstract : The selective oxidation of alkylbenzenes contributes greatly to the production of high-value chemicals. However, developing novel and efficient catalysts remains a great challenge. To explore new and efficient catalysts, a series of POMs of H(4+ n ) SiMo(12− n ) V n O40 (SiMoV n, n = 1, 2 and 3) were reacted with rht -MOF-1 ([Cu6 O(TZI)3 (H2 O)6 ]4 · n H2 O) by a one-pot self-assembly solvothermal method. As a result, three SiMoV n @ rht -MOF-1 (1, n = 1; 2, n = 2 and 3, n = 3) were isolated. Single crystal analysis revealed that SiMoV n were successfully introduced in the cages of rht -MOF-1. When complex 3 was employed as a catalyst, it effectively catalyzed the selective oxidation of alkylbenzene with a conversion of 99% and selectivity of 99% under optimized reaction conditions. Recycling experiments proved that complex 3 is stable and recyclable after six cycles. In comparison with analogous catalysts, complex 3 exhibits outstanding catalytic performance. Furthermore, the kinetics and reaction mechanism were investigated and verified by EPR and XPS analysis. This approach paves a facile route to prepare POMs@MOFs for the selective oxidation of various alkylbenzenes.